Tissue Plasminogen Activator Is Not Involved in Methamphetamine-Induced Neurotoxicity - Ayumi Fukakusa; Hiroyuki Mizoguchi; Hiroyuki Koike; Toshitaka Nabeshima; Kazuhiro Takuma; Kiyofumi Yamada (Elsevier, 2008)
To investigate the role of tissue plasminogen activator (tPA) in methamphetamine (METH)-induced dopaminergic neurotoxicity, we compared the changes in tyrosine hydroxylase (TH) and dopamine transporter (DAT) levels in the striatum after repetitive treatment of METH at 4 mg/kg among wild-type, tPA-deficient (tPA−/−), and protease activated receptor-1-deficient (PAR-1−/−) mice. METH treatment caused a marked decrease in TH and DAT levels in the striatum of those mice with a similar magnitude. No difference in METH-induced abnormal behavior and hyperthermia was observed among the three types of mice. These results suggest that neither tPA nor PAR-1 is involved in METH-induced dopaminergic neurotoxicity in vivo. Keywords:: methamphetamine, neurotoxicity, tissue plasminogen activator